Bartter-Like Syndrome as the Initial Presentation of Dent Disease 1: A Case Report - Chen, Qiaoping; Cao, Yan; Xu, Liyun; Liu, Jingqi; Wu, Xiaochuan (Frontiers in Pediatrics, 2021)
Dent disease is an X-linked recessive renal tubular disorder characterized by low molecular weight proteinuria, hypercalciuria, renal calcinosis, and progressive renal insufficiency. Dent disease with Bartter-like syndrome is rare and can easily be misdiagnosed and mistreated. Herein, we report a case of Dent disease 1 with Bartter-like syndrome as the initial manifestation. The patient was admitted to The Second Xiangya Hospital of Central South University due to polydipsia, polyuria, and weakness of both lower limbs at 2 years of age. Examination results showed that the serum sodium, potassium, and chlorine levels were low, while the level of serum creatinine was normal. The calcium level in the urine was normal. Renal pathological findings showed hyperplasia of the glomerular parabular apparatus. The patient was initially diagnosed with Bartter syndrome, and despite medical interventions, the patient eventually developed chronic renal insufficiency stage 4 at 13 years of age. To determine the cause, the patient was recommended to undergo genetic testing, which showed a CLCN5 gene c. 941C > T mutation (p.S314L), and was finally diagnosed as Dent disease 1. The clinical manifestations of Dent disease are complex and diverse. For patients with atypical clinical manifestations or unsatisfactory therapeutic effects, genetic testing is recommended.